#EstuproNãoÉCulpaDaVítima : as narrativas construídas no twitter sobre o estupro cometido no Rio de Janeiro - Gonçalves, Bianca Bortolon (2018)
On May 25, 2016, the video of a collective rape to an adolescent, held in a community in Rio de Janeiro, was published on Twitter. The fact rose among the users of the social network a debate about the persistence of rape in Brazilian society and culminated in online campaigns against rape culture, a central concept to the feminist movement, guided by the hashtags #EstuproNuncaMais and #EstuproNãoÉCulpaDaVítima. This study aims to analyze the narratives built on Twitter about the collective rape suffered by the teenager on Twitter. Using the perspectivist network analysis methodology proposed by Malini (2016), the main objectives were to understand the ways in which social network users have positioned themselves in relation to the case and to identify the most recurrent themes, as well as to recognize the role of feminist theory in the construction of such narratives. In addition, the matter of cyberspace is introduced as a territory for social activity based on the concepts of territoriality, mass self-communication and the recent history of online demonstrations. After the analysis, it was concluded that the online campaign had a strong influence of the feminist thought but not of the movement itself, having the world of fandoms as a main factor for the campaign’s elevation to a viral status. It was also observed the use of the mentions tool as a way of reporting and, in addition, the high number of users allied to a low number of profile communities and the explosive percentage increase of the use of hashtags as possible data for formulating a virality index of networked campaigns.